Teaching Editions of the Works of Jane Austen: A Survey. - Levy, Michelle; Sharren, Kandice (Texas Studies in Literature & Language)
The article focuses on a survey which analyzes the comprehensiveness of appropriate edition of Jane Austen's novels for an advanced undergraduate course. Topics discussed include collections of Austen's manuscript writings offered by the publisher Norton, contemporary publications on relevant topics by the publisher Broadview, and cost effectiveness of paperback editions.